Penggunaan Whippy Cream Dalam Pembuatan Es Krim Soyghurt - Pangga, Noven Rae; Rossi, Evy; ', Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Soyghurt is fermented products like yoghurt which is made from soya milk by using probiotic bacteria such as Lactobacillus acidophilus and L. bulgaricus. To improve various processed soybean and supports the sale in the community, soyghurt was processed to ice cream. In order to increase low fat in soyghurt ice cream, it should be added vegetable fat, that was whippy cream (W). The aim of this research was to get the best ratio between whippy cream (W) and soyghurt (S) in making soyghurt ice cream. This research was carried out in an experiment by using a Completely Randomized Design (CRD) with five treatments (WS1, WS2, WS3, WS4, and WS5 each for the ratio : 10% W and 90% S, 20% W and 80% S, 30% W and 70% S, 40% W and 60% S, and 50% W and 50% S) with three replications. Data obtained were analyzed statistically using analysis of variance (ANOVA) and if the calculated F is greater than or equal to F table then continued with DNMRT Test at 5% level. The results showed that the combination of W and S in making ice cream significantly improves overrun, melting rate, degree of acidity (pH), total solids, fat and protein content, but decrease the lactic acid bacteria (LAB)content. It can be concluded that the best treatment in making soyghurt ice cream was WS5 treatment (50% Whippy cream and 50% Soyghurt). Keywords : Whippy cream, Ice Cream, Soyghurt,